Anti‐synthetase syndrome associated interstitial lung disease after combination dual immune checkpoint inhibition. Issue 4 (13th March 2023) - Bell, Peter T.; Beaton, Thomas; Terrill, Matthew; Gillis, David; Goddard, John
Abstract: Immune checkpoint inhibitors (ICIs) unleash potent anti‐tumour responses but with frequent off‐target immune‐mediated adverse events (irAE). ICIs can induce a spectrum of rheumatologic manifestations including inflammatory arthritis, Sjögren's syndrome, scleroderma and systemic lupus erythematosus. Here, we describe a case of antisynthetase syndrome associated interstitial lung disease (ILD) following dual Programmed Cell Death 1 and Cytotoxic T Lymphocyte‐Associated Protein 4 checkpoint inhibition in a patient with metastatic melanoma. Initial treatment course was complicated by a number of irAEs including pneumonitis, colitis and thyroiditis. Suspicion of an underlying systemic rheumatic disease was heightened by the severe, relapsing and fibrosing nature of the interstitial pneumonitis. A diagnosis of amyopathic antisynthetase syndrome was made upon detection of circulating aminoacyl‐tRNA synthetase (anti‐EJ) autoantibodies. Intensification of induction immunosuppression followed by maintenance mycophenolate, prednisone and monthly intravenous immunoglobulin achieved long‐term disease control. Detection of de novo ICI‐induced inflammatory myositis ILD requires a high index of suspicion and carries important prognostic and treatment implications. Abstract : In this study, we describe the first reported case of antisynthetase syndrome; characterized by circulating anti‐EJ (glycyl) t‐RNA synthetase antibodies accompanied by relapsing, fibrosing and treatment‐resistant interstitial pneumonitis. This case study highlights the need to also consider rarer phenotypes of ICI‐induced inflammatory lung injury beyond conventional 'ICI pneumonitis' in the diagnostic workup of these patients. Differentiating between rare forms of CTD‐ILD (in particular IIM‐ILD) and conventional 'ICI pneumonitis' has important implications for the expected natural history and optimal treatment paradigms after immunotherapy.